2011
DOI: 10.1162/artl_a_00030
|View full text |Cite
|
Sign up to set email alerts
|

“If You Can't Be With the One You Love, Love the One You're With”: How Individual Habituation of Agent Interactions Improves Global Utility

Abstract: Simple distributed strategies that modify the behaviour of selfish individuals in a manner that enhances cooperation or global efficiency have proved difficult to identify. We consider a network of selfish agents who each optimise their individual utilities by coordinating (or anti-coordinating) with their neighbours, to maximise the pay-offs from randomly weighted pair-wise games. In general, agents will opt for the behaviour that is the best compromise (for them) of the many conflicting constraints created b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 26 publications
1
21
1
Order By: Relevance
“…In the social network domain we have also shown [7] that 'habituating' agents, acting as 'creatures of habit' due to a tendency to increase their preference for the 'status quo', are also formally equivalent to Hebbian learning at the system level and produce global adaptation in the same manner as that shown here. This work frames the utility function as a weighted poly-player coordination game [41,69,73], and the system dynamics as repeated episodes of attempting to reach consensus given constraints amongst players.…”
Section: Related Worksupporting
confidence: 62%
See 2 more Smart Citations
“…In the social network domain we have also shown [7] that 'habituating' agents, acting as 'creatures of habit' due to a tendency to increase their preference for the 'status quo', are also formally equivalent to Hebbian learning at the system level and produce global adaptation in the same manner as that shown here. This work frames the utility function as a weighted poly-player coordination game [41,69,73], and the system dynamics as repeated episodes of attempting to reach consensus given constraints amongst players.…”
Section: Related Worksupporting
confidence: 62%
“…But when agents have the ability to alter who they play with, or the relative strength of their relationships with other agents, this is equivalent to changing the underlying game [72] (or changing how individuals perceive or experience the game [72,7]). Our question is not therefore, whether individual interests are aligned with global interests in the initial game we define, but rather whether the selfish restructuring of the interactions in the system leads, in effect, to agents that (because they are playing a modification of the underlying game) exhibit better alignment with total utility over time.…”
Section: Selfish Changes To Connections and Global Adaptationmentioning
confidence: 99%
See 1 more Smart Citation
“…But in an ecological network this is not the case; reproduction of individuals simply modifies the strategy of the species at that node (and/or the connections the species has with others). We have shown that a games-on-networks model of this type behaves exactly like unsupervised correlation learning (Davies et al 2011; Watson et al 2010a). Moreover, since the total community welfare of a social attractor is correlated with the basin size of the attractor, the changes to connections produced under an individual utility-maximisation principle have the emergent effect of increasing global community welfare (collective fitness) without selection at the system level (Davies et al 2011; Watson et al 2010a)—as per a self-modelling dynamical system.…”
Section: Organisation In Ecological Communities Without Selection At mentioning
confidence: 92%
“…Other studies of games on networks allow individuals to adjust their social ties in a continuous-valued fullyconnected network [50,51]. For example, this might represent how user's perceptions of others change over time [50] or the probability of interaction [52] between two state affects how topology changes State (behavior) Topology (structure) topology affects how state changes players. These changes are equivalent to changing the (effective) strength of a connection or the weighting of a game between two players.…”
Section: Adaptive Networkmentioning
confidence: 99%